PENGUJIAN EFIKASI PENGAWET ANTIMIKROBA PRODUK SKIN CARE X MELALUI UJI TANTANG MIKROBA BERDASARKAN EUROPEAN PHARMACOPOEIA DAN FARMAKOPE INDONESIA SERTA UJI PEMAKAIAN LANGSUNG OLEH PENGGUNA - Halimatussadiyah, Salwa
Skincare is a series of products or practices to support the integrity of skin, improve appearance, and fix the condition of skin. With the skincare industry growing every day, it is essential to include controls to ensure consumer’s safety—one of them being the stability of products during production, storage, and usage. Skincare products have the tendency to be contaminated by microorganisms, which will not only lead to the imbalance of microorganism number, but also impact the physical (change of colour, aroma, and phase) and chemical (decrease of active ingredients concentration and formation of other compounds) characteristics of the product, and health issues for consumers. Contamination of microorganisms can be controlled by means of adding preservatives into the product, normally with maximum concentration of ? 1%, which rises the need of preservatives that are effective to slow the growth of or kill microorganisms. With this in mind, this study aims to determine the efficacy of three formula variations of skincare product X, with different concentration of preservatives phenoxyethanol and chlorphenesin, by means of challenge tests on Pseudomonas aeruginosa, Staphylococcus aureus, Escherichia coli, Candida albicans, and Aspergillus niger, in accordance to European and Indonesian Pharmacopoeia that are commonly used by national cosmetic industries. In addition to this, in-use test a span of 8 weeks is also performed. In use test, formula is transferred and spread onto Tryptone Soybean Agar (TSA) to grow any present contaminating microorganism. Contaminating microorganisms are then identified with simple colony morphology and microscopic observation. Correlation between results of challenge and direct-to-consumer tests are then displayed as Spearman’s rank correlation coefficient. This study concludes that the three formulas pass the efficacy tests in accordance to European and Indonesian Pharmacopoeia, with the most recommended variation being variation 1, followed by variation 2, and then variation 3. Other than that, in variations 1, 2, and 3, Gram-negative bacteria were not found, with in-use test showing that the average amount of total contaminating microorganism of variation 1 < variation 2 < variation 3. Results of efficacy and in-use test show a perfect negative correlation (higher efficacy show lower potential of being contaminated), with a significance at ? 0,01 (2-tailed). Contaminating microorganisms growing on the three formula variations of skincare product X were 26 colony in total and Gram-positive grape-like clusters of cocci that are suspected to Staphylococcus sp. occurred with the highest frequency